2003
DOI: 10.1103/physreva.68.060301
|View full text |Cite
|
Sign up to set email alerts
|

Entanglement and spontaneous symmetry breaking in quantum spin models

Abstract: It is shown that spontaneous symmetry breaking does not modify the ground-state entanglement of two spins, as defined by the concurrence, in the XXZ-and the transverse field Ising-chain. Correlation function inequalities, valid in any dimensions for these models, are presented outlining the regimes where entanglement is unaffected by spontaneous symmetry breaking.PACS numbers: 03.67. Mn, 75.10.Jm Entanglement is a property of a quantum state shared between two or more parties. It is defined with the aim of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
139
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 126 publications
(140 citation statements)
references
References 21 publications
1
139
0
Order By: Relevance
“…It is found that C i,i+1 and ∂C i,i+1 /∂∆ are both continuous at ∆ = 1, and ∂C i,i+1 /∂∆| ∆=1 = 0 (or C i,i+1 reaches its maximum value at ∆ = 1) [5,6]. It is interesting to see how these results can be realized in the present framework.…”
mentioning
confidence: 93%
See 4 more Smart Citations
“…It is found that C i,i+1 and ∂C i,i+1 /∂∆ are both continuous at ∆ = 1, and ∂C i,i+1 /∂∆| ∆=1 = 0 (or C i,i+1 reaches its maximum value at ∆ = 1) [5,6]. It is interesting to see how these results can be realized in the present framework.…”
mentioning
confidence: 93%
“…From Refs. [6,7] and our result, it is clear that QPTs in general can not be distinctly characterized through the analysis of the analyticity properties of concurrence. Moreover, we show that, for the model considered in this paper, the von Neumann entropy remains constant even crossing the critical point.…”
mentioning
confidence: 95%
See 3 more Smart Citations